Hustle Piety and Epistemic Distortion: Redefining Qur’anic Authority in Digital Public Discourse - Langaji, Abbas; Harun, Amrullah; Anggoro, Muhammad Rake Linggar; Azizah, Nur; M. Ilham (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2025)
This study investigates how hustling culture narratives on Instagram mediate and alter Qur’anic authority through mechanisms of epistemic justice. This study seeks to examine the methods, processes, and consequences of selecting and interpreting Qur’anic verses in religious content on Instagram. The study utilises a qualitative design, integrating textual and visual analysis of three intentionally chosen Instagram accounts: : @alqurancustomku, @lanternoflightofficial, and @ssheikh00 that actively participate in productivity and motivational discourse. The approach employs an interdisciplinary framework that incorporates text reception theory, framing theory, hermeneutics, and viewpoints on algorithmic mediation in digital religion. The findings indicate that Qur’anic passages are often decontextualized and deliberately reframed to conform to the principles of hustle culture, emphasising motivational appeal, aesthetic presentation, and audience involvement at the expense of exegetical depth. This approach produces several forms of epistemic distortion, such as selective quoting, oversimplification of meaning, and the use of scripture as a rhetorical tool. The study reveals a notable transition in interpretive authority from conventional religious experts to digital content providers, driven by platform algorithms that enhance visibility and virality. This study theoretically advances the field of digital Islam by introducing the concept of epistemic distortion as a framework for understanding the reconfiguration of religious texts within algorithmic contexts. The text contends that Qur’anic authority is no longer exclusively based on scholarly tradition but is increasingly influenced by platform dynamics, resulting in the phenomenon known as “algorithmic piety.” This reconfiguration signifies wider changes in the interplay between religion, media, and power in the Global South. This study highlights the impact of algorithmic mediation on the sustainability of religious knowledge and authority in contemporary Islam by contextualising local digital activities within global discussions on religion and media